Hubungan Antara Kecerdasan Emosi Dengan Komitmen Organisasi Pada Karyawan - Pramesthi, Anitia Pradsna; , Achmad Dwityanto, S.Psi, M.Si (2017)
The contribution of the most give role to the success of organizations namely human resource factor, meaning that its human quality must be high. In the world of work, someone's commitment to organizations/institutions often become a very important issue, so require si searched the factors. One of the factors that affect organizational commitment is emotional intelligence. The aim of this research is to know the relationship between emotional intelligence with organizational commitment, so the authors propose the hypothesis "there is a positive relationship between emotional intelligence with organizational commitment ". Subjects in this study were employees of PT Kusuma Hadi, Department of printing of 303 subjects, that putting with random cluster sampling. Measuring instrument which is used to reveal research variables there are 2 kinds of measuring instrument, namely: (1) emotional intelligence scale, and (2) the organization commitment scale. Data analysis in this study us s the product moment correlation. Based on the analysis results is obtained correlation between emotional intelligence and organizational commitment (r) of 0.420 with p = 0.000 where p < 0.01, this means there is a very significant positive relationship between emotional intelligence with organizational commitment. That is, the higher the emotional intelligence then the higher organizational commitment on employee, and conversely the lower the intelligence of emotions then the lower organizational commitment on employee anyway. The empirical mean of the emotional intelligence variable amount of 102.06 be compared with hyphothetic mean amount of 102.5. So in generally the employees of PT Kusuma Hadi has medium emotional intelligence. Furthermore the empirical mean of the organizational commitment variable amount of 77.30 be compared with hypothetic mean of 72.5. So in generally the employees PT Kusuma Hadi has emotional intelligence is also medium. The role of emotional intelligence toward the organizational commitment (SE) amount of 17.6% the meaning that there is still 82.4% of other factors beside of the emotional intelligence that influence the organizational commitment.